2004
DOI: 10.1515/jpem.2004.17.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Soy Protein Formulas in Children: No Hormonal Effects in Long-term Feeding

Abstract: Recently, the finding of high plasma concentration of phyto-oestrogens in soy protein formula (SPF) fed children has focused scientific attention on the phyto-oestrogens (isoflavones genistein, daidzein, and their glycosides) contained in SPFs. The aim of this study was to evaluate some hormonal and metabolic effects of long-term (more than 6 months) SPF feeding. We enrolled 48 children, mean age 37 months (range 7-96 months), 27 males and 21 females. All children underwent physical examination. Bone age, urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 15 publications
0
38
0
Order By: Relevance
“…SBIFs provide (Glycine Max) Flour Grown and Processed in Northern Nigeria complete nutrition that adequately supports normal infant growth and development. FDA has accepted SBIFs as safe for use as a good source of nutrition [30].…”
Section: Resultsmentioning
confidence: 99%
“…SBIFs provide (Glycine Max) Flour Grown and Processed in Northern Nigeria complete nutrition that adequately supports normal infant growth and development. FDA has accepted SBIFs as safe for use as a good source of nutrition [30].…”
Section: Resultsmentioning
confidence: 99%
“…These authors also find puberty to be delayed in boys (Den Hond et al, 2002) but they have reported early male puberty more recently (Den Hond et al, 2011). After exposure to phytoestrogens (Adgent et al, 2012;Kim et al, 2011;Strom et al, 2001;Giampietro et al, 2004) or phthalates (Mouritsen et al, 2013;Rais-Bahrami et al, 2004;Mieritz et al, 2012), the findings are also inconsistent: normal or early timing of menarche and normal or early male puberty irrespective of the presumable period of exposure.…”
Section: Critical Windows Of Exposure To Endocrine Disrupters and Timmentioning
confidence: 98%
“…35 Research has shown that there are no adverse effects on human growth, development, or reproduction due to the consumption of soy-based infant formula as compared to conventional cow-milk formula. [36][37] In a clinical studies of infants fed SBIFs [soy-based infant formulas] have resolved questions and raised no clinical concerns with respect to nutritional adequacy, sexual development, neurobehavioral development, immune development, or thyroid disease. SBIFs provide complete nutrition that adequately supports normal infant growth and development.…”
Section: Effect Of Phytoestrogens On Infantsmentioning
confidence: 99%